The Illusion of Spirituality in Legal Professions: Administrative Reductionism and Notary Appointment Integrity in Indonesia - Henry Halim; Imeldalius; Yudadibrata; Novrida Fauziyah Nasution (HM Publisher, 2024)
The Indonesian Law on Notarial Positions places devotion to God Almighty—the principle of spirituality—as the foremost prerequisite for notary appointment, yet rising notarial malpractice signals a disconnect between this transcendental mandate and substantive professional integrity. This convergent mixed-methods socio-legal study examined how regulatory authorities interpret and verify the spirituality requirement, and how stakeholder perceptions of that verification predict support for reform, within a province on the western seaboard of Indonesia governed by Islamic-Malay customary law. The qualitative strand comprised fifteen in-depth interviews and document analysis across three anonymized clusters; the quantitative strand surveyed 185 legal-profession stakeholders using five validated five-point scales (Cronbach’s α 0.81–0.89). Respondents rated administrative reductionism high (mean 4.06, 95% CI 3.97–4.15) and perceived verification adequacy low (mean 2.39, 95% CI 2.28–2.50). Multiple regression explained 60.5% of variance in support for the proposed Spiritual-Integrous Recruitment model (R²=0.605; F(4,180)=68.84, p<0.001; Cohen’s f²=1.53), with administrative reductionism (β=0.312), living-law integration deficit (β=0.242), institutional inertia (β=0.216) and perceived adequacy (β=−0.293) as significant predictors (all p<0.001). Perceived adequacy differed across clusters (ANOVA F(2,182)=6.90, p=0.001, η²=0.07), lowest in the resource-rich semi-urban cluster. Qualitative themes—administrative reductionism, institutional inertia, and disconnect from living law—triangulated the survey. The state secularizes an ethical mandate into a documentary checklist, marginalizing integrity. The study proposes the Spiritual-Integrous Recruitment model, integrating psychometric integrity testing with living-law screening, to convert a dogmatic illusion into a measurable safeguard of legal professionalism.